Agroclimatic landscapes of pergamon: Modeling agricultural suitability of an ancient city and its environs. - Robert Busch; Anne Dallmeyer; Ulrike Herzschuh; Felix Pirson; Brigitta Schütt; Fabian Becker (PLoS ONE)
The relationship between humans and the natural environment is shaped by the perception, utilization, and management of natural resources. In the Mediterranean region, the cultivation of resources has played a crucial role in shaping landscapes over time. Assessing the potential of landscapes for using various natural resources provides insights into the functioning of socio-ecological systems and highlights areas susceptible to environmental fluctuations and human exploitation. The environs of Pergamon - the ancient capital of the Pergamene Kingdom and later a major Roman city in Asia Minor - serve as an exemplary case of human-environment interaction in Western Anatolia. This work reconstructs the climatic potential for cultivating annual crops commonly used in Mediterranean rainfed agricultural systems, focusing on the Pergamon micro-region. Paleoclimate simulations from MPI-ESM 1.2 with high spatial resolution T63 (~1.875° x 1.875° on a gaussian grid) were integrated into the EcoCrop niche model to explore spatio-temporal changes in agricultural suitability from 400 BCE to 400 CE. The results highlight the consistent agricultural potential of the western Bakırçay plain due to its favorable climatic conditions. In contrast, the eastern plain and surrounding foothills exhibit greater variability, necessitating adaptive land management strategies. Comparisons with a pollen-based reconstruction confirmed the general alignment in climatic trends, supporting the plausibility of the modeled scenarios. Favorable conditions may have sustained agricultural productivity but also highlight dependencies on regional trade networks, decoupling Pergamon's economy from local subsistence agriculture and introducing vulnerabilities to trade disruptions. This study challenges the notion of a uniform "Roman" Climate Optimum, highlighting the importance of understanding local agroclimatic conditions and adaptive land management strategies in ancient societies.